DEVELOPING CONTEXTUAL LESSON PLANNING TO ENGAGE STUDENTS’ UNDERSTANDING IN THE ROLE OF GENDER IN LANGUAGE USED IN DAILY LIFE - Tiara Retno Haryani (Reforma : Jurnal Pendidikan dan Pembelajaran, 2016)
Language is not only simply a means of communicating information, but also means of establishing and maintaining relationship with other people (Trudgil, 2000). In social life, the first thing that you will notice is the gender of the person we met. It is a fundamental and obvious thing before we can have an interaction or communication with somebody else. The objective of the activity is to direct the students in understanding the role of gender in language for daily life more deeply. The students are expected to be able analyze the language phenomena in their daily life. The activity is started by explaining the materials to the students about gender role, gender bias, and gender dialect used. The second step is that grouping the students and asks them to discuss about the phenomena of gender in language used in their society so that they know how the characteristic of each gender in their society. The last step is discussing the results together in class. This activity is probably appropriate for the advanced learners, such as university students. It can gain the students’ knowledge and raising the students’ confident in stating their opinion in discussion. Keywords: contextual, lesson planning, role of gender